Analysis of Social Perception and Tourism Potential of Traditional Villages in Zhanjiang Based on Sustainability Eyes by Big Data, RS and GIS - He, Chunying; Wang, Yun-Shang; Wang, Ruei-Yuan (International journal of Rural Development, Environment and Health Research, 2023)
The traditional village is not only the biggest heritage of agriculture but also the most ancient and precious resource of culture in China. But along with the rapid development of modern society and cities, the traditional village, which has a science of study, history, and cultural value, is disappearing rapidly. Therefore, this paper uses big data and ArcGIS as a means to obtain the research data of traditional villages in Zhanjiang and analyze their spatial distribution characteristics. Then, the driving factors affecting the tourism development of traditional villages are analyzed, and the social perception behind them is interpreted. Finally, the Tourism Development Potential Index (TDPI) model is used to evaluate the tourism development potential of traditional villages in Zhanjiang and make suggestions. The results showed that among the factors affecting the tourism development of traditional villages in Zhanjiang, the weight of human factors was greater than that of natural factors. Among the eight driving factors of tourism development, high-level scenic spots and socio-economic factors had the greatest impact on tourism development in traditional villages, with 10 traditional villages with strong potential, 47 with medium potential, and 39 with weak potential. Based on this, the corresponding development strategy is proposed, aiming at offering a scientific basis for developing Zhanjiang Traditional Village's tourist industry.